2013
DOI: 10.1016/j.jegh.2012.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the silent epidemic of malnutrition in Palestinian preschool children

Abstract: None.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
2
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 16 publications
1
8
2
2
Order By: Relevance
“…These data show that the prevalence of malnutrition in children from these regions of Asia is higher than that of Iranian children. A meta-analysis, including 17 studies in Palestine, showed that the prevalence of underweight, short stature and slimness in children under the age of five was 4.7%, 10.9%, and 2.9%, respectively [50]. This study reported a lower prevalence of malnutrition indices compared to our study.…”
Section: Discussioncontrasting
confidence: 52%
“…These data show that the prevalence of malnutrition in children from these regions of Asia is higher than that of Iranian children. A meta-analysis, including 17 studies in Palestine, showed that the prevalence of underweight, short stature and slimness in children under the age of five was 4.7%, 10.9%, and 2.9%, respectively [50]. This study reported a lower prevalence of malnutrition indices compared to our study.…”
Section: Discussioncontrasting
confidence: 52%
“…The prevalence of stunting in Palestine increased from 7.5% in 2000 to 10.9% in 2010 with the Gaza Strip recording a stunting prevalence of 10.4% (23 (24). In recent years, stunting has been the most prevalent form of undernutrition (~10%) as compared to underweight and wasting in Gazan children under 5 years (24,25). Our study showed that stunting prevalence at 24 months was 2 times greater than reported in previous studies (23)(24)(25), although underweight and wasting rates prevalence were similar.…”
Section: Discussioncontrasting
confidence: 47%
“…Several studies have used meta-analyses in order to accurately calculate the prevalence of a disease as recorded in the literature, 13,15,16 and recently one study used the same methodology to accurately determine the prevalence of obesity among Greek children. 13 Analyses were performed with Comprehensive Meta-Analysis software V2.0 (Biostat Inc, Englewood, NJ, USA).…”
Section: Statistical Analysesmentioning
confidence: 99%